Taxation, credit constraints and the informal economy - Julia P. Araujo; Mauro Rodrigues (EconomiA, 2016)
This paper extends Evans and Jovanovic (1989)'s entrepreneurship model to incorporate the informal sector. Specifically, entrepreneurs can operate either in the formal sector – in which they have limited access to credit markets and must pay taxes – or in the informal sector – in which they can avoid paying taxes, but have no access to credit markets. In addition, technology in the informal sector is both less productive and more labor intensive than that in the formal sector. We calibrate the model to the Brazilian economy, and evaluate the impact of credit frictions and taxation on occupational choices, aggregate output and inequality. Removing all distortions can improve aggregate efficiency considerably, largely because this induces entrepreneurs to switch to the formal sector, where the technology is superior. Most of this effect comes from removing credit market frictions, but taxes on formal businesses are also important. The elimination of distortions can also reduce income inequality substantially. – – Este trabalho incorpora o setor informal ao modelo de empreendedorismo de Evans e Jovanovic (1989). Especificamente, empreendedores podem operar no setor formal - com acesso limitado ao mercado de crédito e sujeitos a cobrança de impostos - ou no setor informal - evitando a tributaç\~ao, mas sem acesso a crédito. Adicionalmente, a tecnologia no setor informal é menos produtiva e mais intensiva em trabalho. O modelo é calibrado com base em dados da economia brasileira. Avaliam-se os efeitos de tributos e de restriç\~oes no mercado de crédito sobre as escolhas ocupacionais, produç\~ao agregada e desigualdade. A remoç\~ao de todas as distorç\~oes melhora a eficiência agregada de maneira considerável, principalmente por conta da migraç\~ao de agentes para o empreendedorismo formal, que opera com uma tecnologia superior. A restriç\~ao de crédito possui o maior efeito, mas os impostos sobre empresas formais também têm papel importante. A eliminaç\~ao de distorç\~oes ainda permite reduzir substancialmente a desigualdade de renda no modelo.
Keywords: 330; Informal sector; Credit frictions; Taxation; Entrepreneurship; Setor informal; Restriç\~oes de crédito; Taxaç\~ao; Empreendedorismo